Predictive diagenetic clay-mineral distribution in siliciclastic rocks as a tool for identifying sequence boundaries in non-marine successions: the Coalspur Formation, west-central Alberta - Khidir, Ahmed; Catuneanu, Octavian (Wydawnictwo Naukowe UAM, 2009)
The study of upper Cretaceous – lower Tertiary fluvial deposits of the Coalspur Formation in the Foothills region of west-central Alberta reveals that the distribution of early authigenic kaolinite has a well-defined relation to the sequence stratigraphic framework. In this context, it has been observed that the kaolin mineral content increases in sandstones lying below subaerial unconformities, which mark the most significant stratigraphic hiatuses and hence the sequence boundaries in fully fluvial successions. The increased abundance of authigenic kaolinite immediately below sequence boundaries may have been caused by the infiltration of meteoric water during times of subaerial erosion, resulting in the dissolution of unstable minerals (e.g., micas and feldspar) and the formation of kaolinite and secondary porosity. It is therefore suggested that the change in clay mineral assemblages in the stratigraphic section depends in part on the position of the analyzed sandstone samples relative to the sequence boundaries. In a larger context, the method of using authigenic clays to delineate depositional sequences in non-marine successions needs to be evaluated on a case-by-case basis, as the diagnostic early diagenetic minerals underlying the sequence boundary may change as a function of palaeoclimate and also as a function of late diagenetic processes.
Keywords: Sequence stratigraphy; Non-marine deposits; Siliciclastics; Diagenesis; Clay minerals